(untitled) (Research, Society and Development, 2021)
Pregnancy is a natural physiological process understood by the sequence of adaptation that takes place in the woman’s body from fertilization. The preparation of the body for a pregnancy involves some physiological adjustments, where it presents a great increase of hormones causing a ligamentous loosening and mechanical changes in the skeleton and biomechanics. (Mantle and Polden, 2005). As a result of pregnancy, discomfort, pain and changes in the musculoskeletal system are frequent. Throughout history, people who had a more active lifestyle during the gestation period had more benefits at the time of childbirth. National and international organizations, and with technological and medical advances, seeking to provide pregnant women with safety during pregnancy, encourage them to practice physical exercise, aiming to promote health, avoiding maternal and fetal mortality. The physiotherapist is an adequate professional to alleviate gestational symptoms, working with preventive measures. The present study was based on a descriptive bibliographic research, which seeks to demonstrate the importance of the physiotherapist during the gestational period and the postpartum period. The practice of exercises during pregnancy is essential, as it improves physical conditioning, helps with metabolism, reduces edema, works on breathing and conditions the body for labor. Through the research carried out, it is noted that the physiotherapist plays an important role both in the gestational period and in the postpartum period, through techniques that improve pain, body posture, contribute to childbirth, minimizing injuries to the pelvic floor.